2022
DOI: 10.1186/s13071-022-05160-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of culture-dependent native microbiota in Zika virus infection in Aedes aegypti

Abstract: Background Emerging and re-emerging vector-borne diseases (VBDs) pose a recurring threat to tropical countries, mainly due to the abundance and distribution of the Aedes aegypti mosquito, which is a vector of the Zika, dengue, chikungunya, and yellow fever arboviruses. Methods Female 3–5 day-old Ae. aegypti were distributed into two experimental groups: group I—survey of cultivable bacteria; sucrose group: fed only on sucrose, i.e., non-blood-fed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Other studies in Ae. aegypti and murine models have shown that ZIKV infection modifies the structure of gut bacterial communities, decreasing their diversity and richness [ 25 , 81 , 84 ]. Interestingly, our PERMANOVA analysis with both factors, infection and resistance, showed only infection influenced bacterial diversity; this analysis is novel for Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in Ae. aegypti and murine models have shown that ZIKV infection modifies the structure of gut bacterial communities, decreasing their diversity and richness [ 25 , 81 , 84 ]. Interestingly, our PERMANOVA analysis with both factors, infection and resistance, showed only infection influenced bacterial diversity; this analysis is novel for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti with experimental ZIKV infection have found associated bacterial taxa such as the families Rhodobacteraceae and Desulfuromonadaceae and the genera Cellulosimicrobium, Elizabethkingia, Enterobacter, Pseudomonas, and Staphylococcus ; in Ae. albopictus , Elizabethkingia anophelis was associated with ZIKV infection [ 25 , 84 , 96 ]. Additionally, E. anophelis and Lysinibacillus reduced ZIKV infection, affecting vector competence [ 84 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serratia bacteria can modulate the vector competence of populations of Ae. aegypti for the Zika virus by interfering with mosquito salivation [ 69 ] and interfering in the vectorial capacity of other mosquito species [ 70 ]. In this study, Serratia 16S readings were found in one female of each species, Sa.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the main bacteria isolated from the midgut of A. aegypti were Acinetobacter spp., Aeromonas spp., Cedecea spp., Cellulosimicrobium spp., Elizabethkingia spp., Enterobacter spp., Lysinibacillus spp., Pantoea spp., Pseudomonas spp., Serratia spp. and Staphylococcus spp., 72% of them Gram-negative [ 55 ]. Thus, it is possible to notice a great variability of genera that infect Aedes spp., despite some of these being identified in more than one study.…”
Section: Formation and Composition Of The Microbiomementioning
confidence: 99%